18F-FDG PET/CT surveillance for the detection of recurrence in patients with head and neck cancer. (February 2017) - Kim, Shin-Ae; Roh, Jong-Lyel; Kim, Jae Seung; Lee, Jeong Hyun; Lee, Sang Hoon; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Background: Posttreatment detection of recurrence may lead to salvage treatment and prognostic prediction in patients with head and neck squamous cell carcinoma (HNSCC). We evaluated the diagnostic and prognostic values of 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) after definitive treatment of HNSCC. Methods: This prospective study included 278 consecutive patients who underwent curative surgery ( n = 143, 51.4%) or definitive radiotherapy/chemoradiotherapy ( n = 135, 48.6%) for previously untreated HNSCC. The patients were regularly followed up and evaluated by 18 F-FDG PET/CT, head and neck CT/magnetic resonance imaging (MRI), and chest CT at regular intervals after treatment. The imaging interpretations were compared with the histological results for recurrence. Receiver operating characteristics curves analysis, McNemar's test and logistic regression using generalised estimating equations were used to compare the diagnostic accuracy of 18 F-FDG PET/CT and standard imaging of CT/MRI or chest CT, and a Cox proportional hazards model was used to assess the prognostic value of PET/CT. Results: During a median follow-up of 44 months (range, 24–62 months), 73 patients (26.3%) had recurrence or persistent diseases. The area under curves for 18 F-FDG PET/CT and CT/MRI were 0.975 (0.964–0.992) and 0.789 (0.713–0.874), respectively ( P < 0.001). 18 F-FDG PET/CT detected 65 of 66 recurrences (98.5%) not suggested by physical examination and endoscopy. Positive findings on 18 F-FDG PET/CT scans were independent predictors of poorer cancer-specific and overall survival outcomes ( P < 0.01). Conclusions: Posttreatment 18 F-FDG PET/CT surveillance helps to properly detect recurrence and to predict the survival following treatment of HNSCC. Highlights: 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) surveillance detected recurrences more sensitively than CT/magnetic resonance imaging or chest CT. Many recurrences (66/93, 71.0%) remained undetected by regular outpatient examination. Most recurrences (65/66, 98.5%) were correctly found by posttreatment 18 F-FDG PET/CT. Positive posttreatment PET/CT findings are independent predictors of poor survival outcomes.